Applying model-based testing to network monitor user interface - Panday, Ashish (Kansas State University, 2010)
This report is a case study of applying Model-Based testing approach using SpecExplorer, which is a model-based testing tool developed by Microsoft, to test a component of Microsoft Network Monitor. The system under test is the UI of the Network Monitor feature, Parser Profiles Management. Model-Based testing is a methodology for automated testing which not only automates the test execution, but the test design and generation. This approach starts by expressing an abstract model of the system which is a smaller subset of the product behavior, but retains essential elements which form the focus of the testing problem. A model-based testing tool creates a finite state machine from the model which is traversed to produce test cases. Thus, it provides more efficient coverage and flexibility in developing and maintaining test cases.
Keywords: Model based testing; User Interface Automation; SpecExplorer; Test automation; Microsoft; UI automation strategies; Computer Science (0984)